Ca2+/pH-triggered gelation of Pickering emulsion in vitro digestion: Visualization and sustained-release performance. (July 2023) - Liu, Haifang; Huang, Riting; Zhao, Xinyu; Yang, Shujuan; He, Furui; Qin, Wenqi; Huang, Junhao; Yu, Gaobo; Feng, Yuhong; Li, Jiacheng; Liao, Chenghong
Abstract: The emulsion gels transformed by Pickering emulsions have great potential as a novel platform for oral drug delivery. In this study, an innovative alginate-based fluorescent colloidal particle was synthesized by Ugi reaction with alginate and carbon dots, which can stabilize Pickering emulsion at the present of Ca 2+ . The Pickering emulsions were converted to emulsion gels during gastric digestion. The microstructure of interfacial film was characterized in situ with confocal laser scanning microscopy. In the process of simulated gastrointestinal digestion, phase conversion of the Pickering emulsion was observed directly in situ by an automatic living cell imaging system. The results showed that clear fluorescent interfacial films can be visualized after simulated oral digestion, and fluorescent spheres were appeared after gastrointestinal digestion, indicating that Pickering emulsions were transformed into emulsion gels. Moreover, results on cell viability and cell uptake showed that the Pickering emulsion had good biocompatibility, which could be taken up by Caco-2 cells and could sustain the release of the drug. The formation of emulsion gels delays the digestion rate and improves the stability of encapsulated curcumin (CUR). In particular, in situ visualization technique also has promising applications in the digestion process and cellular uptake. Graphical abstract: Image 1 Highlights: Fluorescent colloidal particle was obtained by carbon dots grafted with alginate. The amphiphilic colloidal particles can stabilize Pickering emulsion well. The gelation of Pickering emulsion in the stomach phase was triggered by Ca 2+ /pH. The interface film, structural changes and cell uptake could be visualized in situ. The Pickering emulsion loaded curcumin and showed the sustained-release property.